2016
DOI: 10.1089/thy.2016.0046
|View full text |Cite
|
Sign up to set email alerts
|

Spine Stereotactic Radiosurgery for Patients with Metastatic Thyroid Cancer: Secondary Analysis of Phase I/II Trials

Abstract: SSRS for thyroid metastases as a primary or adjuvant/salvage therapy is well tolerated and yields high rates of local control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Some papers have reported that spine SBRT achieved good local control even for the so-called radioresistant histopathologies, including sarcoma, 20 thyroid cancer, 21 renal cell carcinoma, 22 and melanoma. 16 The biological rationale for these observations may be explained by experimental data suggesting that only high-dose-per-fraction SBRT, typically exceeding 8 to 10 Gy per fraction, activates pathways to enhance cell death, particularly via the sphingomyelinase pathway within tumor endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have reported that spine SBRT achieved good local control even for the so-called radioresistant histopathologies, including sarcoma, 20 thyroid cancer, 21 renal cell carcinoma, 22 and melanoma. 16 The biological rationale for these observations may be explained by experimental data suggesting that only high-dose-per-fraction SBRT, typically exceeding 8 to 10 Gy per fraction, activates pathways to enhance cell death, particularly via the sphingomyelinase pathway within tumor endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] EBRT is a palliative treatment indicated only when pain, risk of fracture, and neurological complications of spinal cord compression are present. [ 12 14 ] Radioiodine therapy is considered the first-line treatment for sodium-iodide symporter (NIS) positive metastatic lesions. TSH suppression therapy intends to reduce the impetus for further tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated thyroid carcinoma (DTC) is one of the primary pathogenic tumors associated with the development of spinal metastases. 1 DTC is the most common thyroid carcinoma representing 90% of cases overall, consisting of papillary carcinoma (70-75%) and follicular carcinoma (15-20%). 2 The prognosis of patients with thyroid carcinoma is good, and the 10-year survival rate is around 90%; however, the presence of distant metastases is related to a significant reduction in life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…2 The prognosis of patients with thyroid carcinoma is good, and the 10-year survival rate is around 90%; however, the presence of distant metastases is related to a significant reduction in life expectancy. 1 Indeed, up to 68% of thyroid carcinoma patients develop spinal metastases and the clinical prognosis of this group of patients is poor. [3][4][5][6][7] The presence of metastatic spinal differentiated thyroid carcinoma (MSDTC) significantly increases the incidence of complications and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation